Secure love : create a relationship that lasts a lifetime - Menanno, Julie (Simon & Schuster, 2024)
"What does a healthy relationship look like? Create a lasting and loving attachment with the help of the expert couple's therapist behind the popular Instagram account @TheSecureRelationship." -- Publisher annotation.